Mechanical properties of nacre and highly mineralized bone - Currey, John D.; Zioupos, Peter; Peter, Davies; Casinos, Adrià (Royal Society, 2001)
We compared the mechanical properties of ‘ordinary’ bovine bone, the highly mineralized bone of the rostrum of the whale Mesoplodon densirostris, and mother of pearl (nacre) of the pearl oyster Pinctada margaritifera. The rostrum and the nacre are similar in having very little organic material. However, the rostral bone is much weaker and more brittle than nacre, which in these properties is close to ordinary bone. The ability of nacre to outperform rostral bone is the result of its extremely well–ordered microstructure, with organic material forming a nearly continuous jacket round all the tiny aragonite plates, a design well adapted to produce toughness. In contrast, in the rostrum the organic material, mainly collagen, is poorly organized and discontinuous, allowing the mineral to join up to form, in effect, a brittle stony material.